Effectiveness of Probiotic Phaeobacter Bacteria Grown in Biofilters Against Vibrio anguillarum Infections in the Rearing of Turbot (Psetta maxima) Larvae - Prol García, María Jesús; Pintado, José (Marine Biotechnology, 2013)
13 páginas, 5 figuras, 3 tablas The rearing environment of first-feeding turbot lar- vae, usually with high larvae densities and organic matter concentrations, may promote the growth of opportunistic path- ogenic Vibrionaceae bacteria, compromising the survival of the larvae. The aim of this study was to assess the effectiveness of the biofilm-forming probiotic Phaeobacter 27-4 strain grown on a ceramic biofilter (probiofilter) in preventing Vibrio anguillarum infections in turbot larvae. In seawater with added microalgae and maintained under turbot larvae rearing conditions, the probiofilter reduced the total Vibrionaceae count and the concentration of V. anguillarum , which was undetectable after 144 h by real-time PCR. The probiofilter also improved the survival of larvae challenged with V. anguillarum , showing an accumulated mortality similar to that of uninfected larvae (35 – 40 %) and significantly ( p <0.05) lower than that of infected larvae with no probiofilter (76 %) due to a decrease in the pathogen concentration and in total Vibrionaceae. Furthermore, the probiofilter improved seawater quality by decreasing turbidity. Phaeobacter 27-4 released from the probiofilters was able to survive in the seawater for at least 11 days. The bacterial diversity in the larvae, analysed by denaturing gradient gel electrophoresis, was low, as in the live prey (rotifers), and remained unchanged in the presence of V. anguillarum or the probiofilter; however, the probiofilter reduced the bacterial carrying capacity of the seawater in the tanks. Phaeobacter- grown biofilters can constantly inoculate probiotics into rearing tanks and are therefore potentially use- ful for bacterial control in both open and recirculating indus- trial units. María J. Prol-García obtained a grant from the I3P Program of CSIC, co-financed by European Social Fund. Research funding was also provided by INIA (ACU03-003) and by the I3 Program of the Spanish Ministry of Education and Science (CSIC-PIE 2006 7 01067 Peer reviewed